The Authority of the Indonesia Deposit Insurance Corporation (LPS) to File Bankruptcy Petitions Against Controlling Shareholders of Non-Systemic Failed Banks - Diana R.W. Napitupulu (Greenation Research & Yayasan Global Resarch National, 2025)
This article examines the legal authority of the Indonesia Deposit Insurance Corporation (Lembaga Penjamin Simpanan/LPS) to file bankruptcy petitions against controlling shareholders of non-systemic failed banks. The issue arises from the need to recover state funds used in bank resolution while simultaneously upholding fundamental principles of corporate and insolvency law, particularly limited liability and legal certainty. Using normative juridical research, this study analyzes statutory provisions governing deposit insurance, banking supervision, and bankruptcy, complemented by doctrinal analysis and relevant legal principles in financial regulation. The article argues that the authority of LPS to initiate bankruptcy proceedings against controlling shareholders constitutes a special legal mechanism that departs from the general concept of shareholder immunity. Such authority is designed to prevent moral hazard, ensure accountability of bank owners, and protect public interests embedded in the stability of the financial system. In the context of non-systemic failed banks, this mechanism reflects a policy choice to prioritize efficient recovery of resolution costs without triggering broader systemic risk. However, the exercise of this authority raises several legal challenges. First, ambiguities remain regarding the scope and limits of LPS’s standing before the Commercial Court, particularly in establishing a direct causal link between the actions of controlling shareholders and the bank’s failure. Second, the interaction between the LPS Law and the general Bankruptcy and Suspension of Debt Payment Law creates potential tensions concerning procedural safeguards and the principle of due process. Third, inconsistent interpretation of shareholder liability may undermine predictability in judicial practice. This article concludes that while the authority of LPS to file bankruptcy petitions against controlling shareholders of non-systemic failed banks is legally justifiable as a lex specialis regime, its implementation requires clearer statutory standards and more consistent judicial interpretation. Strengthening these aspects is essential to balance public financial protection with the rule of law and shareholder rights.